2018
DOI: 10.1080/02770903.2018.1445266
|View full text |Cite
|
Sign up to set email alerts
|

Is recurrent respiratory infection associated with allergic respiratory disease?

Abstract: RRI is associated with previous atopic diseases, and these conditions should be considered when treating children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Food allergy has been reported in around 25% of children with asthma, allergic rhinitis in 60%, atopic dermatitis in 45% and recurrent respiratory tract infections in 60%. [6][7][8][9][10] Atopic comorbidities and recurrent respiratory tract infections are associated with increased asthma morbidity. Children with asthma and food allergy have increased asthma symptoms and a significantly lower lung function compared to asthmatic children without food allergy.…”
Section: Introductionmentioning
confidence: 99%
“…Food allergy has been reported in around 25% of children with asthma, allergic rhinitis in 60%, atopic dermatitis in 45% and recurrent respiratory tract infections in 60%. [6][7][8][9][10] Atopic comorbidities and recurrent respiratory tract infections are associated with increased asthma morbidity. Children with asthma and food allergy have increased asthma symptoms and a significantly lower lung function compared to asthmatic children without food allergy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, findings might be affected by respiratory infections, recall bias, and gender. Epidemiological studies have found an association between respiratory tract infection and risk of allergic rhinitis [40,41]. Acetaminophen exposure for such episodes could cause confounding.…”
Section: Discussionmentioning
confidence: 99%
“…the previous studies, the factors which related to the recurrent URTI are social economy status, exposure to cigarette smoke, rickets, immunization status, family history, older siblings in the family, nutritional status, breastfeeding, cardiovascular disease, and congenital disease in respiratory tract. [7][8][9][10][11][12] These risk factors may be used for recurrent infection control program in children. Therefore, this study aimed to understand the risk factors which influence the occurrence of recurrent upper respiratory infection in children aged 3-60 months at primary healthcare centers (Puskesmas) in Gresik.…”
Section: Original Articlementioning
confidence: 99%